Manajemen Sumber Daya Manusia dalam Meningkatkan Daya Saing UMKM: Studi Kasus Khanza Fashion Store - Mesaria Zendrato; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze the implementation of human resource management in enhancing the competitiveness of SMEs at Khanza Fashion Store Ambarawa, Semarang Regency. The problem focuses on how human resource management practices applied by the business owner contribute to operational effectiveness, service quality, and business sustainability. To address this issue, the study adopts theoretical perspectives on human resource management and business competitiveness that emphasize human resources as strategic organizational assets. Data were collected through in-depth interviews with the business owner and employees, direct observation of daily operational activities, and supporting documentation, and were analyzed qualitatively using thematic analysis. The findings indicate that human resource management at Khanza Fashion Store is implemented in a simple, flexible, and contextual manner, yet it effectively supports the improvement of employee skills, work motivation, and service quality. Harmonious working relationships and a personal approach to employee motivation foster loyalty and work commitment, which in turn strengthen the firm’s competitive position. This study concludes that human resource management plays a strategic role in enhancing SME competitiveness, even though it has not been implemented through formal and well-documented management systems.